Political taste in the Slow Food movement - Siniscalchi, Valeria (E|C, 2020)
In these pages I will address the question of taste and its roles within the Slow Food movement as an example of "food activism": with this term I mean both the more or less structured actions of groups of consumers and/or producers and the movements with a complex internal organization. I worked on the Slow Food movement carrying out an ethnography of the headquarters, in Italy and of some political and economic nodes, such as the French structure (Slow Food France) or the events that Slow Food organizes on food issues: Cheese, the Salone del Gusto, Terra Madre, Slow Fish.